2015
DOI: 10.17795/nmsjournal26731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Osteoporosis Prevention Program Based on Health Belief Model Among Females

Abstract: Background:Several studies reported the efficacy of osteoporosis prevention interventions in improvement of people’s preventive behaviors. However, there are reports that the interventions were not successful in altering osteoporosis health beliefs and preventive behaviors.Objectives:The current study aimed to assess the effect of a program based on health beliefs model (HBM) on females’ health beliefs and performances about osteoporosis preventive behaviors.Patients and Methods:This quasi-experimental study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
8
34
0
1
Order By: Relevance
“…The results of the study are consistent with the results by Ebadi Fard Azar et al (5) and Khani Jeihooni et al (29).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study are consistent with the results by Ebadi Fard Azar et al (5) and Khani Jeihooni et al (29).…”
Section: Discussionsupporting
confidence: 92%
“…[26] Furthermore, the present study results showed that most of nurses in Egypt and Sudan did not intake calcium supplement. Despite [27] in Saudi Arabia who conducted similar study to evaluate effectiveness of education using the HBM (health believe model) in preventing osteoporosis found that the majority of the nurses were low perceived calcium intake barriers, however there was non-significant decrease in the barriers due to unhealthy nutritional habits.…”
Section: Discussionmentioning
confidence: 99%
“…The most pertinent models and theories addressing adherence research relevant to the management of diabetes in Haitian Americans are the health belief model (HBM), the social cognitive theory (SCT), and the transtheoretical model (TTM). According to Sirur, Richardson, Wishart, and Hanna () and Jeihooni, Hidarnia, Kaveh, and Hajizadeh (), the theories most commonly used today for issues of compliance and health promotion are the HBM and the SCT. As mentioned previously, although adherence and compliance were first theorized by Haynes et al.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…The HBM is a psychological model developed by Rosenstock in the 1950s (Irwin, ; Jeihooni et al., ). According to the HBM as discussed by Irwin (), for a change to occur, the individual must be ready.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%